EVALUATING NURSES’ TRAINING REQUIREMENTS, PRACTICE PATTERNS, AND BARRIERS IN INTRAVENOUS MEDICATION PREPARATION AND ADMINISTRATION: INSIGHTS FROM A TERTIARY HOSPITAL IN PALESTINE - Shalabi, Israa Rajeh (An-Najah National University, 2025)
Background: Intravenous (IV) medication is a task that requires a high level of attention. When administering and preparing IV medications, mistakes can be made that have lethal consequences. Importantly, sufficient training is needed to explain certain elements of IV administration, particularly the difficulties faced by nurses. In a tertiary hospital in Palestine, this study evaluated the training requirements, practice behaviors, and obstacles faced by nurses when preparing and administering IV medications. Methods: A cross-sectional descriptive study was conducted with 216 nurses in a tertiary hospital. Instruments, which are validated self-administered questionnaires covering demographic details, knowledge, attitudes, practices and barriers, were used. The statistical analysis was performed via IBM SPSS. Mann‒Whitney U tests, Kruskal‒Wallis tests, and Spearman correlations were used to examine associations between variables. Results: The results showed that nurses had average confidence in the IV administration of medicines. Gender, age, and educational background did not significantly differ. The level of knowledge was positively correlated with English proficiency (r=0.183; p=0.026), indicating that a better performer on English tests scored better in the knowledge assessment. Some of the internet librarians registered weak positive correlations with knowledge (r=0.145; p=0.056), showing that having access to the internet to obtain resources could strengthen the level of knowledge. The attitudes toward IV medicine administration were rated positively by most of the respondents, with median and interquartile range (IQR) values of 21 and interquartile ranges of 19-21. The years of service yielded a slight positive correlation with the attitude score (r=0.151; p=0.049). Notably, internet access was moderately positively correlated with attitudes (r=0.245; p≤0.01), implying that easier access to digital resources makes nurses more confident in how they practice. With respect to practice behavior, ICU nurses performed slightly better concerning IV administration protocol adherence than their counterparts in inpatient wards did (p = 0.019). English proficiency had a moderate positive correlation with practice scores (r = 0.168, p = 0.033), whereas internet availability was associated most strongly with higher practice behavior scores (r = 0.312, p < 0.001). The most common barriers cited were workload and time constraints, with nurses in urban environments reporting heavier workloads than those in rural areas did (p = 0.004). A statistically significant negative correlation was found between knowledge and barriers perceived by respondents (r = -0.207, p = 0.006), meaning that better knowledge reduces the perception of barriers to IV administration. Internet access had the strongest negative correlation with the perception of knowledge barriers (r = -0.231, p < 0.001), meaning that online access reduces training needs. Conclusions: Despite the existing positive attitudes of nurses and their adherence to IV administration and medication protocols, systematic barriers and knowledge gaps have been revealed, particularly regarding workload, time, and resources. These observations further suggest that proficiency in English, internet access, and experience all aid in the knowledge, attitudes, and practices of nurses. These challenges should be highlighted through the provision of education programs and resources to encourage nurse competency and safe patient practice.
تقييم متطلبات تدريب الممرضين، أنماط الممارسة، والعوائق في تحضير وأعطاء الأدوية الوريدية: رؤى من مستشفى ثلاثي في فلسطين